Die Frauenbewegung : ihre Ziele und ihre Bedeutung - Krukenberg, Elsbeth Conze, 1867- (Historische Quellen zur Frauenbewegung und Geschlechterproblematik, 1905)
This discussion of the feminist movement concentrates primarily on questions of education and employment and provides in an appendix an overview of the 190 women organizations included in the Bund deutscher Frauenvereine.